The Relationship between Parenting Patterns and Student Learning Motivation with Social Studies Learning Outcomes of Grade VI Students in Elementary School Cluster XIV, Buleleng District - Ina Triarsitadewi, Ida Ayu; Basilius Redan Werang; Ketut Herya Darma Utami (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the problem of low learning motivation among students in Social Studies (IPS), which has an impact on learning outcomes. The main objective of this study was to examine the relationship between parenting patterns and learning motivation with IPS learning outcomes among elementary school students. This study was a quantitative study with an ex post facto design. The research subjects involved 148 sixth-grade students from several elementary schools in one cluster. Data were collected using questionnaires to measure parental parenting patterns and learning motivation, as well as documentation of students' social studies learning outcomes. The instruments were tested for validity and reliability. Data analysis was performed using multiple regression techniques. The results of the study indicate that there is a positive and significant relationship between parental parenting patterns and social studies learning outcomes, as well as between learning motivation and social studies learning outcomes. These findings suggest that parental parenting patterns and learning motivation are important factors contributing to students' academic achievement. The implications of this study emphasize the importance of parental involvement in creating a supportive learning environment and the need to strengthen learning motivation in the educational process.